Knowledge and its Association with Menstrual Hygiene Practices Among School Going Adolescents of Tokha Municipality: 10.55131/jphd/2024/220104 - Bhatt, Ashish; Devkota, Elisha (Journal of Public Health and Development, 2023)
Menstrual hygiene is crucial for women's health and well-being, but societal acceptance of menstruation remains a significant issue in Nepal. Despite government efforts to reduce stigma, the health of women, children, and adolescents is still affected by its widespread superstitions. As a result, studies on menstrual knowledge and hygiene practices among adolescents in Nepal are scarce. The primary goal of this study is to further understand the depth of adolescent girls' knowledge about menstruation and its association with menstrual hygiene practices. In order to address this, we performed a descriptive cross-sectional study in Tokha municipality of Kathmandu as the study area. The study population consisted of female teenagers studying in randomly selected schools. A total of 404 samples were collected. Statistical significance of the association between the independent and dependent study variables were assessed using the chi-square test and logistic regression. We found that about 78.5% of the total of respondent had knowledge about menstruation, and mothers were main source of information. Menstrual practices, such as type of material used (AOR=2.549 95%CI= 1.078-6.710), frequency of cleaning genitalia at least two times (AOR=1.639; 95% CI=1.214-6.328), at least 3 times (AOR= 3.119; 95% CI=1.429-9.328) and product used to clean genitalia (AOR= 0.623 95%CI= 1.429-9.328) were associated with knowledge of respondents. It can be stated that teenage schoolgirls generally have decent knowledge about menstruation. Menstrual health issues are a concern that has to be addressed. Our study implicates that adolescent menstrual hygiene practices are associated with menstrual knowledge.